Manajemen Kepemimpinan Transformasional Di Bidang Pendidikan Terhadap Kedisiplinan Mutu Pendidikan - Hanik Fauziyah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
The principal applies the transformasional leadership style of leadership that is able to motivate followers to more than transcend their own immediate self-interest in order to jointly translate the mission and vision of the organization and be able to transform the energy resources, human, instrument, or situation to achieve the goal of school reform. Transformasional leadership is a leadership that is able to create fundamental changes based on religious values, systems and cultures to create the innovation and creativity of its followers in order to achieve a defined vision. The results of this study agree with Bass and Avolio that the transformasional leadership model involves four dimensions with concepts; idealized, influence, inspirational motivation, intellectual simulation and individualized consideration.